Interferentes eritrocitários e ambientais na anemia falciforme - Naoum, Paulo C. [UNESP] (Elsevier, 2000)
Erythrocytes and environmental interferences on sickle cell anaemia Sickle cell anaemia runs na extremely variable clinical course At one end of spectrum, it is characterized by a crippling haemolitic anaemia, interspersed with severe exacerbations, or crises, yet it may be an extremely mild disorder, which is found only by chance on rotine haematological examination. The reasons are only partly understood for these remarkable differences in phenotypic expression of what appears to be the same genetic defect: they include the level of Hb Fetal, coinheritance of the alpha thalassaemia and of other genetic variantsthat has influence as genetic modulation in sickle cell anaemia. However, other genetics abnormalities of erythrocytes: G-6PD deficiency, spherocytosis and deficiencies of anti-oxidant enzymes(SOD, GPx and Catalase) probably interfereon the clinical course of sickle cell anaemia. The haplotypes of the chromosome (Bantu, Benin, Camaroon and Arab-Indian) bearing the sickle gene is associated with assorted haematological and clinical features that are likely, at least in part, to be mediated throgh effects on Hb Fetal concentration. Beyond these factors characterizes as erythrocytes interferents, there are the environmental interferents. Between environmental interferents become detached the socio-economic and cultural situation of each patient. These aspects have influence on the life of affected individuals including social interactions, family relations, peer interaction, intimate relationships, education, enployment, violence, spiritual attitudes and navigating complexities of the health care system, providers and their ancillary functions. As a result of this article it is proposed a protocol of laboratorial management of sickle cell syndrome with detach to sickle cell anaemia.
Keywords: Environmental interferences; Erythrocytes interferences; Sickle cell anaemia